The catalytic function of cytochrome P450 is entwined with its membrane-bound nature [version 1; referees: 4 approved] - Carlo Barnaba; Katherine Gentry; Nirupama Sumangala; Ayyalusamy Ramamoorthy (F1000Research, 2017)
Cytochrome P450, a family of monooxygenase enzymes, is organized as a catalytic metabolon, which requires enzymatic partners as well as environmental factors that tune its complex dynamic. P450 and its reducing counterparts—cytochrome P450-reductase and cytochrome b5—are membrane-bound proteins located in the cytosolic side of the endoplasmic reticulum. They are believed to dynamically associate to form functional complexes. Increasing experimental evidence signifies the role(s) played by both protein-protein and protein-lipid interactions in P450 catalytic function and efficiency. However, the biophysical challenges posed by their membrane-bound nature have severely limited high-resolution understanding of the molecular interfaces of these interactions. In this article, we provide an overview of the current knowledge on cytochrome P450, highlighting the environmental factors that are entwined with its metabolic function. Recent advances in structural biophysics are also discussed, setting up the bases for a new paradigm in the study of this important class of membrane-bound enzymes.